Pengaruh Service Quality Terhadap Customer Sati Sfaction pada PT Pelabuhan Indonesia (Persero) Sub Regional Bali Nusa Tenggara Cabang Benoa - Ni Putu Radha Savitri Maheswari Putri; Gede Pradiva Adiningrat; Ida Bagus Artha Adnyana (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of Service Quality on Customer Satisfaction at PT Pelabuhan Indonesia (Persero) Sub Regional Bali Nusa Tenggara, Benoa Branch. Service Quality was measured using the five dimensions of Service Quality: tangibles, reliability, responsiveness, assurance, and empathy. A quantitative research method was employed, utilizing a survey of 100 respondents consisting of domestic and international ship passengers at Benoa Port. Data was collected through questionnaires and analyzed using multiple linear regression and hypothesis testing (t-test and F-test). The results indicate that all five dimensions of service quality have a positive and significant partial effect on customer satisfaction. Simultaneously, these dimensions also significantly influence customer satisfaction, with a coefficient of determination (R²) of 73.9%. Among the dimensions, reliability was found to be the most dominant factor affecting customer satisfaction. These findings provide practical implications for the management of Benoa Port to enhance service quality, particularly in reliability, physical facilities, and staff responsiveness, to achieve higher customer satisfaction.